Pengaruh Etnis Tionghoa terhadap Pilihan Pekerjaan: Studi Kasus di Kalangan Pekerja di Jakarta - Ciek Julyati Hisyam; Diva Kayla Nazwa Anas; Ghazy Aldifa Afti; Sifah Fauziah (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to investigate the influence of Chinese ethnicity on job choices among workers in Jakarta. Using a case study approach and qualitative methods, this research was conducted in May 2024 involving 5 sources. Data was collected through interviews, observation and document analysis. The research results show that factors such as cultural values, social networks, and historical experiences play an important role in influencing the occupational choices of ethnic Chinese in Jakarta. Apart from that, society's perception of Chinese ethnicity also influences career choices. The favorable socio-economic dynamics of the Chinese community in Jakarta also play an important role in shaping their career choices. It is hoped that this research can provide a deeper understanding of the factors that influence the career choices of ethnic Chinese in Jakarta, as well as their relevance to the cultural, social and economic aspects that influence the relationship between ethnic Chinese and the world of work in the Indonesian capital. Thus, this research provides an important contribution in expanding insight into the dynamics of the relationship between Chinese ethnicity and employment choices in urban contexts such as Jakarta.